Analysis of the use of CMUcam5 Pixy camera in wheeled soccer robots. Issue 1 (May 2020) - Nasution, T H; Simon, A; Fahmi, F; Tanjung, K; Zarlis, M; Noer, N
Abstract: Wheeled soccer robot is a robot that can play football like humans but maneuvers using wheels. Wheeled soccer robot has an event that is held routinely every year in Indonesia, namely in the Indonesian Robot Contest. To play well, the robot is certainly equipped with sensors and actuators that are qualified. One of the sensors used is the camera. The camera on the soccer robot functions to capture images around the robot that will later be processed on a computer. In this study, we analyzed the use of CMUcam5 Pixy for wheeled soccer robots. testing is carried out as much as 2 stages, namely testing without noise and testing with noise. From the results of tests that have been carried out, the CMUcam5 Pixy camera has a certain limit for detecting the ball. In testing with CMUcam5 Pixy camera noise can only detect up to 490 cm. Whereas in testing with CMUcam5 Pixy camera noise can only detect up to 420 cm.